2004
DOI: 10.1530/eje.0.151s003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic defects in GH synthesis and secretion

Abstract: Growth hormone (GH) is a multifunctional hormone produced in the anterior pituitary that promotes postnatal growth of skeletal and soft tissues. GH secretion and release are complex phenomena depending on several intrinsic and extrinsic factors modulating the release of two hypothalamic hormones, GH releasing hormone and somatostatin. Any genetic or acquired disorder that impairs GH secretion or action causes a pathological phenotype characterized by harmonic short stature with isolated GH deficiency (IGHD) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Growth hormone deficiency origins from a variety of disorders, e.g., genetic (reviewed in [213]) and acquired conditions resulting in various clinical symptoms with short stature in childhood and the adult GH deficiency syndrome (reviewed in [214]). A corner stone in the diagnosis of GHD is the GH response to a standardized stimulation test [109,110].…”
Section: Ghdmentioning
confidence: 99%
“…Growth hormone deficiency origins from a variety of disorders, e.g., genetic (reviewed in [213]) and acquired conditions resulting in various clinical symptoms with short stature in childhood and the adult GH deficiency syndrome (reviewed in [214]). A corner stone in the diagnosis of GHD is the GH response to a standardized stimulation test [109,110].…”
Section: Ghdmentioning
confidence: 99%
“…This genetically heterogeneous condition can be explained by mutations within key genes of the somatotroph axis, namely GH1 that encodes the growth hormone (GH), as well as GHSR and GHRHR, which encode the GH secretagogue receptor and the receptor of the GH releasing hormone (GHRH), respectively (Alatzoglou et al, 2009;Birla et al, 2016;Mullis, 2010;Pantel et al, 2006;Wajnrajch, Gertner, Harbison, Chua, & Leibel, 1996). Depending on studies, 5-30% of the cases for which a molecular cause has been found are familial (Alba et al, 2004;Bona, Paracchini, Giordano, & Momigliano-Richiardi, 2004;Lindsay, Feldkamp, Harris, Robertson, & Rallison, 1994). The GHRHR encodes a 423-amino-acid protein, which is a member of the secretin family of G-protein coupled receptors (GPCR).…”
Section: Introductionmentioning
confidence: 99%
“…GHRH acts on GHRH receptor (GHRH-R) located in the plasma membrane of anterior pituitary somatotrophic cells and signals the somatroph to synthesise and secrete GH. Thus GH deficiency (GHD) can result from genetic defects in GH1 gene which codes for pituitary GH and GHRH-R gene coding for the GHRH receptor [1]. GHRH-R mutations are reported to be the cause of approximately 10% of isolated growth hormone deficiency with an autosomal recessive inheritance [2].…”
Section: Growth Hormone (Gh) Is Under Stimulatory and Inhibitory Contmentioning
confidence: 99%